The Influence of Alliance Experience on Acquisition Premiums and Post-acquisition Performance - Cho,Sam Yul; Arthurs,Jonathan (Journal of Business Research, 2018)
This paper examines the influence of acquirers’ alliance experience on acquisition outcomes. Specifically, we investigate whether or not acquirers with alliance experience pay higher acquisition premiums and achieve improved post-acquisition performance. We also investigate how the impact of acquirers’ alliance experience is contingent on the alliance portfolios of target firms. We find that acquirers with alliance experience pay higher acquisition premiums but lower acquisition premiums when their target firms possess alliance portfolios of greater size or diversity. We also find that such acquirers achieve higher post-acquisition performance when the size of alliance portfolios of target firms is larger. Overall, this study suggests that alliance experience can help acquirers develop organizational knowledge and capabilities, and thus influence acquisition outcomes.
Keywords: Strategy & Entrepreneurship